Answer:
dodododododododo
Step-by-step explanation:
Dividing the first equation by 2
X + 2y = 12
Dividing the equation 2 by 4
-3x + 2y = -4
subtracting both equations
4x = 16
X = 4
Also 4 + 2y = 12
2y = 8
Y = 4
Please mark as brainliest
Wait isn’t it 30 or am I reading it wrong?
Answer:
C
Step-by-step explanation:
noting that
= i
Given
![\sqrt{-80}](https://tex.z-dn.net/?f=%5Csqrt%7B-80%7D)
= ![\sqrt{16(-1)(5)}](https://tex.z-dn.net/?f=%5Csqrt%7B16%28-1%29%285%29%7D)
=
×
× ![\sqrt{5}](https://tex.z-dn.net/?f=%5Csqrt%7B5%7D)
= 4i
→ C